Antitumor Effect of Fibrinogen Microparticles Containing Adriamycin on Ehrlich Ascites Carcinoma in Mice - MIYAZAKI, SHOZO; HASHIGUCHI, NORIO; YOKOUCHI, CHIZUKO; TAKADA, MASAHIKO; HOU, WEI-MIN (Chemical & pharmaceutical bulletin, 1986)
The antitumor activity of fibrinogen microparticles containing adriamycin against Ehrlich ascites carcinoma in mice was evaluated on the basis of animal survival data. Tumor cell injections were performed on day 0 and microparticle injections on day 1, both intraperitoneally. A prolongation of the life span of tumor-bearing mice following injection of therapeutic microparticles was noted, and the microparticles containing adriamycin were therapeutically more effective than adriamycin alone. The high chemotherapeutic efficiency of fibrinogen-adriamycin microparticles was striking at high doses which would be toxic in the case of the drug alone. These results indicated that fibrinogen microparticles containing adriamycin may be effective in cancer chemotherapy. Microparticles composed of fibrinogen could be a novel drug carrier for use in injectable delivery systems for anticancer agents.